ENERGY CONSUMPTION MODEL OF WIRELESS SENSOR NET NODES AND ITS APPLICATION FOR INCREASING NETWORK OFFLINE OPERATION TIME - Mohammed Neamah Mohsen; Igor Vladimirovich Boguslavskiy (Advanced Engineering Research, 2014)
A proposed new model of the wireless sensor net can be applied for the network optimized energy efficiency. The optimization of the communication structure between nodes taking into account the capacity of the power supply unit, the amount of the information collected and transmitted by the node, as well as the energy connectivity between nodes and its quantitative assessment contributes to this. The application of this model will allow optimizing the structure of energy consumption in a wireless network to increase the time of its offline operation. (It is a case of life to the first node failure due to the power supply exhaustion.) The presented model is given in terms of the graph theory. The research relevance is proved. The approach to the problem solution based on the solution to the corresponding linear programming problem is described. The implementation of solutions in the form of a computer program is considered. The computer simulation results are described. The conclusions regarding the applicability of the technology in practice are provided.